Multicentre European study of thalamic stimulation for parkinsonian tremor: a 6 year follow-up. Issue 6 (26th September 2007) - Hariz, M I; Krack, P; Alesch, F; Augustinsson, L-E; Bosch, A; Ekberg, R; Johansson, F; Johnels, B; Meyerson, B A; N'Guyen, J-P; Pinter, M; Pollak, P; et al.
Abstract : Aim: To evaluate the results of ventral intermediate (Vim) thalamic deep brain stimulation (DBS) in patients with tremor predominant Parkinson's disease (PD) at 6 years post surgery. Methods: This was a prolonged follow-up study of 38 patients from eight centres who participated in a multicentre study, the 1 year results of which have been published previously. Total scores as well as scores for individual items of the motor part and the disability part of the Unified Parkinson's Disease Rating Scale were used for evaluation. Results: Tremor was still effectively controlled by DBS and appendicular rigidity and akinesia remained stable compared with baseline. Axial scores (speech, gait and postural instability), however, worsened, and in parallel the initial improvement in activities of daily living scores at the 1 year follow-up had disappeared at 6 years, despite sustained improvement of tremor. Remarkably, neither daily doses of dopaminergic medication nor fluctuations and dyskinesias had changed at 6 years compared with baseline in this particular patient group. Conclusion: This study confirms that patients with tremor dominant PD who do not present with fluctuations and dyskinesias may have a relatively benign progression of the disease. Vim DBS, although having no effect on akinesia and rigidity, is a relatively lenient surgical procedure and may still have a place for long term symptomatic control of PD tremor in selected patients.